Legal Analysis of Development in Organizational Ambidexterity in Higher Education Institutions - Harjono, Dhaniswara K.; Soebagio, Atmonobudi (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Ambidexterity plays an important role in organizational development, which influences national development. National development is a joint effort between the people and the state which is carried out in order to improve themselves in a better direction together. The aim of this research is to analyze the law of organizational amidecsterity development in higher education institutions. This research is part of a qualitative research using a systematic review approach. Systematic review is a method that uses previous evidence-based evidence through review, evaluation, structured evaluation, classification and categorization. The results of the research analysis show that the ambidexterity of higher education institutions is a model that integrates the performance determinants of classy higher education institutions, and proposes a commitment that is influenced by: (a) brand ambidexterity, which is explorative and exploitative oriented; (b) able to adapt to the social and economic environment; and (c) being responsive to students' perceptions of the university's brand image and reputation which will increase their commitment to their studies. The implication of this research is to provide an overview to higher education institutions so they can develop the concept of ambidexterity in the process of implementing higher education.